PENGARUH PEMBERIAN LIMBAH CAIR TAHU DAN PUPUK UREA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max L.(Merill) - Efrida Lubis; Darmawati ,; Mhd Arif Hidayat Srg (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
This research aims to determine the effect of waste water Soyabean and Urea fertilizer on growth and yield of soybean (Glycine max L.(Merrill). Implemented on Jl. KusumaSampali District of Percut Sei Tuan Medan, with altitude of ±25meters above sea level in April toJuly 2013 with a randomized block design (RBD) Factorial. factorthe firstisthe Liquid Waste Soyabean(T) consists of 3 levels is to (without giving) T1(7.5 ml/plot) and T2 (15 ml/plot). Factor both is Urea Fertilizer(U) consists of 3 levels is U0 (without giving), U1(7.5 g/ plant), and U2 (15 g/ plant). Repeated three times. Results of the study that the administration of liquid waste out effect parameters significantly affect plant height, number of branches, days to flowering, weight of 100 seeds. Whereas urea fertilizer and their interaction effect did not differ significantly affected parameters, number of branches, days to flowering, number of podsper plot, weight of 100 seeds.Keywords: waste water soyabean, urea fertilizer, growth, product